2019
DOI: 10.1039/c8ra09584a
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid synthesis of zirconium oxycarbide nanopowders with defined and controlled composition

Abstract: A combined synthesis strategy involving a carbothermal reduction and gelation approach with glycine as gelating agent was used to obtain Zr-based (oxy)carbide materials with defined and controlled composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Recent studies 8,11,12,20,25 have shown a linear relationship or polynomial relationships between lattice parameter and C/Zr atomic ratio and it is remarkable that the authors presenting this new correlations were working on either ZrC x 8,11,12 or ZrC x O y 20,25 . Zhou et al 26 discuss the difficulties encountered for the determination of carbon and nitrogen inclusions in ZrC x using XRD and they confirmed the expected usefulness of neutron diffraction to determine accurately carbon and oxygen stoichiometries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies 8,11,12,20,25 have shown a linear relationship or polynomial relationships between lattice parameter and C/Zr atomic ratio and it is remarkable that the authors presenting this new correlations were working on either ZrC x 8,11,12 or ZrC x O y 20,25 . Zhou et al 26 discuss the difficulties encountered for the determination of carbon and nitrogen inclusions in ZrC x using XRD and they confirmed the expected usefulness of neutron diffraction to determine accurately carbon and oxygen stoichiometries.…”
mentioning
confidence: 99%
“…Zhou et al 26 discuss the difficulties encountered for the determination of carbon and nitrogen inclusions in ZrC x using XRD and they confirmed the expected usefulness of neutron diffraction to determine accurately carbon and oxygen stoichiometries. However, neutron diffraction could not or was not used for the characterization of ZrC x specimens in other literature 8,[11][12][13][14]20,25 , obviously because this technique is quite difficult to access (only ~20 facilities worldwide having an external users program 27 ). Other techniques such as Raman spectroscopy that could be used to detect the presence of microcrystalline carbon or amorphous carbon in carbide systems 28,29 , or X-ray photoelectron spectroscopy (XPS) that can also help distinguish the nature of bonds present in the sample, if the metal in the carbide is bonded with carbon, oxygen 30 or nitrogen 31 , are not often used within the ceramic processing community.…”
mentioning
confidence: 99%
“…Generally, higher faradaic current densities are measured with carbon Vulcan XC-72R, which is visible after normalization of the current with respect to the geometrical (see Figure 3) and the BET surface areas of Vulcan (250 m 2 g À 1 ) [34] and ZrO 0.31 C 0.69 (350 m 2 g À 1 ) [30] (see Figure S3, supporting information). The differences in the CVs show that the ZrO 0.31 C 0.69 cannot be entirely covered with the excess carbon from the synthesis process.…”
Section: Resultsmentioning
confidence: 91%
“…The differences in the CVs show that the ZrO 0.31 C 0.69 cannot be entirely covered with the excess carbon from the synthesis process. [30] Comparison of the cathodic potential region from À 0.6 V to 0 V for both ZrO 0.31 C 0.69 and carbon shows that the ZrO 0.31 C 0.69 is more active in the potential region where the HER takes place, resulting in an earlier HER onset potential and in higher current densities compared to carbon. At anodic potentials of > 1.8 V carbon shows high anodic currents with an earlier onset compared to that of ZrO 0.31 C 0.69 , suggesting an active dissolution of carbon at these high potentials.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation